Art since 1960. - Archer, M. (London : Thames and Hudson, 1997)
During the past forty years, profound and multifarious changes have taken place in art : stylistic divergence has become the prevailing characteristic. This intelligently argued survey explores the perennial question - art's relationship to everyday life - which links Pop, Minimal, Conceptual, Land, Performance, Body and Installation art and myriad developments in the work of Warhol, Beuys, Bourgeois and the many other artists whose works are discussed and illustrated. With a timeline that shows movements, key figures and important world events at a glance, and a full bibliography Art Since 1960 provides a unique and indispensable overview and source of information on the evolution of art over the past four decades.
Abramovic, Marina ; Acconci, Vito ; Andre, Carl ; Anselmo, Giovanni ; Araeen, Rasheed ; Arman ; Art & Language ; Asher, Michael ; Atlkinson, Terry ; Aycock, Alice ; Baldessari, John ; Barry, Judith ; Barry, Robert ; Baselitz, Georg ; Basquiat, Jean-Michel ; Becher, Bernd & Hilla ; Benglis, Lynda ; Beuys, Joseph ; Bickerton, Ashley ; Bloom, Barbara ; Boltanski, Christian ; Bourgeois, Louise ; Broodthaers, Marcel ; Buren, Daniel ; Calle, Sophie ; Caro, Anthony ; Chamberlain, John ; Chicago, Judy ; Christo & Jeanne-Claude ; Clemente, Francesco ; Cragg, Tony (Anthony) ; César ; Deacon, Richard ; Douglas, Stan ; Espaliú, Pepe ; Finlay, Ian Hamilton ; Fischl, Eric ; Flanagan, Barry ; Fleury, Sylvie ; Fritsch, Katharina ; Fury, Gran ; Gilbert & George ; Gober, Robert ; Golub, Leon ; Gonzalez-Torres, Felix ; Graham, Dan ; Graves, Nancy ; Guston, Philip ; Haacke, Hans ; Halley, Peter ; Hammons, David ; Haring, Keith ; Hatoum, Mona ; Hesse, Eva ; Hill, Gary ; Hiller, Susan ; Hirst, Damien ; Hockney, David ; Hodgkin, Howard ; Holzer, Jenny ; Horn, Rebecca ; Huebler, Douglas ; Höfer, Candida ; Immendorff, Jörg ; Johns, Jasper ; Judd, Donald ; Kabakov, Ilya ; Kawara, On ; Kelley, Mike ; Kelly, Ellsworth ; Kelly, Mary ; Kiefer, Anselm ; Kienholz, Ed ; King, Phillip ; Kippenberger, Martin ; Klein, Yves ; Koons, Jeff ; Kossoff, Leon ; Kosuth, Joseph ; Kounellis, Jannis ; Kusama Yayoi ; Lawler, Louise ; LeWitt, Sol ; Levine, Sherrie ; Lichtenstein, Roy ; Long, Richard ; Louis, Morris ; Lueg, Konrad ; Lüpertz, Markus ; Manzoni, Piero ; Mapplethorpe, Robert ; Matta-Clark, Gordon ; McCracken, John ; Merz, Mario ; Miss, Mary ; Moore, Frank ; Morley, Malcolm ; Morris, Robert ; Mucha, Reinhard ; Nauman, Bruce ; Newman, Barnett ; Noland, Kenneth ; Oldenburg, Claes ; etc.
boek